Living life with an electric touch - Caputi, A.A. (2023)
The electric organ discharges (EODs) produced by weakly electric fish have long been a source of scientific intrigue and inspiration. The study of these species has contributed to our understanding of the organization of fixed action patterns, as well as enriching general imaging theory by unveiling the dual impact of an agent’s actions on the environment and its own sensory system during the imaging process. This Centenary Review firstly compares how weaklyelectric fish generate species- and sex-specific stereotyped electric fields by considering: (1) peripheral mechanisms, including the geometry, channel repertoire and innervation of the electrogenic units; (2) the organization of the electric organs (EOs); and (3) neural coordination mechanisms. Secondly, the Review discusses the threefold function of the fish-centered electric fields: (1) to generate electric signals that encode the material, geometry and distance of nearby objects, serving as a short-range sensory modality or ‘electric touch’; (2) to markemitter identity and location; and (3) to convey social messages encodedinstereotypical modulations ofthe electric field that might be considered as species-specific communication symbols. Finally, this Review considers a range of potential research directions that are likely to be productive in the future.